Media Group Network on digital: news construction from the hybrid perspective - Firmantoro, Verdy; Sarwono, Billy K.; Irwansyah (Faculty of Communications Science, Dr. Soetomo University, 2022)
Advances in information technology provide new opportunities and demand changes, one of which is in the construction of news. Digital media has also changed the landscape and the structure of the quality of the press, which prioritises emotional rather than rational aspects. As a result, the relationship between the media and the public is increasingly complex. This study aims to analyse the news in the Media Group Network newsroom as a news media from the perspective of a hybrid media system. This research is a qualitative study using an in-depth interview with the Editorial Board of the Media Group Network and journalists from Media Indonesia, Metro TV and Medcom.id, as well as a literature overview from related research and media content. The study results show that public mood affects the news construction process. Issue sensitivity tends to get more attention which contains shared values. There are three implications of influencing public mood in reporting: increasing democratic involvement, decentralising news sources, and influencing policy-making in the newsroom.